EVALUASI KINERJA STRUKTUR BETON BERTULANG DENGAN DAN TANPA DILATASI (Studi Kasus: Gedung Lapas Perempuan Tabanan) - Putra, Putu Bagus Sayudha; Sukrawa, Made; Susila, I Gede Adi (Program Studi Magister Teknik Sipil Universitas Udayana, 2026)
The Women's Correctional Facilty (Lapas) building in Tabanan is a multi-storey building with a total length of 51.45 m which is designed using a twin column dilation system. Generally, dilation is applied to buildings with irregular floor plans or lengths exceeding 60 m. Considering that this building has a regular floor plan and less than 60 m span, the effectiveness of using dilation needs to be evaluated to improve efficiency without reducing structural safety. This study compares the performance of the Model with Dilation (MDD) and Model Without Dilation (MTD) against earthquake, thermal, and concrete shrinkage loads. The analysis was carried out using SAP2000 with the Dynamic Response Spectrum and Static Nonlinear Pushover Analysis (SNPA) methods based on SNI 1726:2019 and ATC-40. The thermal load was modeled with ΔT = 4.67°C and concrete shrinkage with a strain of εsh = −0.0003. The results show a maximum ratio MTD deviation of 0.52%, which is below the allowable limit of 0.77%, and both models achieved the Immediate Occupancy (IO) level. Shrinkage analysis increased the MTD beam reinforcement requirement by 21% without any dimensional changes. In terms of efficiency, MTD reduced concrete volume by 8%, making the dilation-free design more optimal, safe, and economical.